2000
DOI: 10.1097/00002030-200009290-00013
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of expanded HIV counselling and testing in primary care settings: a first look

Abstract: Routine testing is the most cost-effective approach to identifying new HIV infections. However, using risk histories may be similarly cost-effective under various assumptions. Both routine testing and using risk histories are more cost-effective than current practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 47 publications
0
24
0
1
Order By: Relevance
“…7,8 Although we and others previously evaluated the cost-effectiveness of screening, [9][10][11][12] these analyses were performed before HAART became available. Because both the costs and the benefits of screening have changed since these analyses were published, the current cost-effectiveness of screening and the settings in which screening is economically attractive remain uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Although we and others previously evaluated the cost-effectiveness of screening, [9][10][11][12] these analyses were performed before HAART became available. Because both the costs and the benefits of screening have changed since these analyses were published, the current cost-effectiveness of screening and the settings in which screening is economically attractive remain uncertain.…”
mentioning
confidence: 99%
“…n engl j med 352;6 www.nejm.org february 10,2005 cost-effectiveness of screening for hiv n engl j med 352;6 www.nejm.org february 10,2005 The new england journal of medicine n engl j med 352;6 www.nejm.org february 10,2005 cost-effectiveness of screening for hiv…”
mentioning
confidence: 99%
“…Such persisting levels of HIV infection suggest, as recently debated [28][29][30], the need of adopting routine HIV screening strategies -instead of risk-based testing policies -in the low-risk heterosexual population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have further demonstrated that expanded HIV counseling, testing, and referral in the primary care setting has a projected incremental cost of $4200 per infection identified and potential for cost savings over the long-term [38]. Estimates of unmet prevention needs in the United States suggest additional investments of $817 million to over $1.85 billion will be needed and will be overwhelmingly offset by the averted costs of medical care [39].…”
Section: Cost-effectiveness Of Routine Hiv Testingmentioning
confidence: 99%